Upaya Meningkatkan Hasil Belajar Peserta Didik Kelas VII-3 SMP Negeri 5 Sabang Materi Pecahan Melalui Penerapan Model Pembelajaran Kooperatif TGT - Ady Safwan (Idealmathedu: Indonesian Digital Journal of Mathematics and Education, 2019)
This study aims to improve the learning result of grade VII.3 students of SMP Negeri 5 Sabang on fraction topic by applying TGT (Team Games Tournament) cooperative learning model. This is a type of classroom action research consisting of two cycles. The data collection was carried out on August to October 2018, while subject of the study is grade VII.3 students. Data collection technique applied in this study is tests and observations. Quiz tests are carried out to determine the students’ learning result individually while observations are conducted to find out the teacher's activities during implementing TGT cooperative learning model. Descriptive analysis was chosen as the technique of data analysis. Score analysis was carried out by analysing the standard achievement of minimum satndard score 70. The average score of students in the first cycle was 25.89, the highest score was 57. Meanwhile, the average score of the second cycle decreased to 7.46 with the highest score 33. The research result indicates that there has not been an increase in students’ learning result in fraction topic by applying TGT cooperative learning model. In conclusion, it can be stated that that the application of the TGT cooperative learning model in learning fractions in class of VII-3 SMP Negeri 5 Sabang cannot help teachers to improve students’ learning result.